Preparation and anti-colon cancer effect of a novel curcumin analogue (CA8): in vivo and in vitro evaluation - Wen, Jie; Zhao, Lingmao; Li, Zhuohan; Pi, Chao; Feng, Xianhu; Shi, Peng; Yang, Hongru; Chen, Ligang; Wang, Xiaodong; Liu, Furong; Wei, Yumeng; Zhao, Ling (Frontiers in Pharmacology, 2024)
Chemotherapy remains the first choice of treatment for colon cancer despite the inevitable adverse effects. Curcumin (CU) possesses antitumor activity but has poor aqueous solubility, low bioavailability, and weak activity. To address this, nine novel monocarbonyl CU analogues were designed, synthesized, and evaluated in the present study. Among them, CA8 exhibited the highest water solubility, which was approximately 2.37×10 6 times that of CU. In addition, compared with CU, its cytotoxicity on Caco-2 cells (19.2 times/48 h) was stronger. Of note, CA8 arrestedthe cell cycle of Caco-2 cells at the G2/M phase and induced apoptosis. Meanwhile, acute toxicity experiments indicated that KM mice tolerated CA8 for up to 300 mg/kg CA8 (oral administration) and 50 mg/kg CA8 (intraperitoneal injection). The oral administration of CA8 to Sprague Dawley rats exhibited higher AUC (0-t) (6.23-fold) and longer MRT (0-t) (3.35-fold) than that of CU. CA8 also inhibited the proliferation and angiogenesis of tumor cells more than CU and tegafur. Finally, CA8 may exert antitumor effects through the activation of JNK pathway and inhibition of AKT pathway.These results suggest that CA8 is a safe and highly effective new drug for colon cancer treatment.